Quality Of Artificial Feed Using Koro Bean (Canavalia Ensiformis) As A Substitute Of Soybean Flour For Sand Lobster Feed (Panulirus Homarus) - Reffi Aryzegovina; Ira Desmiati; Siti Aisyah (Barakuda'45, 2022)
One type of legume that is very suitable to be used as a raw material for making lobster feed is the sworded koro nut (Canavalia ensiformis). Soybeans which are a source of vegetable protein can now be supported by sword beans. The purpose of this study was to examine the quality of artificial feed using Koro Sword Nuts (Canavalia ensiformis) as a substitute for soybean flour for Sand Lobster (Panulirus homarus) feed. The method used is the experimental method with RAL using 4 treatments and 3 replications. The treatments in this study were A (artificial feed without sword koro beans (control)), B (2.5% sword koro beans in 1 kg artificial feed), C (3% sword koro beans in 1 kg artificial feed), and D ( 3.5% sword koro beans in 1 kg of artificial feed). Research data were analyzed using non-parametric Kruskal Wallis statistical test and described. The test animal used was the Sand Lobster (Panulirus homarus) with a size of 8-10 cm with an average weight of 200-300 grams. The results of the physical test showed that the parameters of breaking speed, level of hardness, level of homogeneity and attractiveness were significantly different from the use of Peanut Koro Sword flour, while the parameters of sinking speed and deliciousness were not significantly different. The results of the proximate chemical test of feed using the best swordfish flour was in feed B, which contained 9.34% Moisture Content, 11.87% Ash Content, Crude Protein (N x 6.25) 29.98%, Crude Fat 6, 84 %, Carbohydrates 41.92% and Crude Fiber 5.00 %.